Physical, Chemical, and Mechanical Characterization of Coated Date Palm Leaf Fiber from the Middle Region of Iraq for Potential in Civil Engineering Application - Noor S. Al-Hassnawi,; Mastura Azmi,; Mohammed Y. Fattah,; Fauziah Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Date palm leaf fibers are suitable for engineering applications due to their availability, inexpensiveness, and ecofriendliness. However, there is a risk of biodegradation in the long term. This paper explores date palm leaf fiiber (DPL) properties and the protection of the fibers from biodegradation to enhance their lifespan. To this end, two coating materials (bitumen and polyurethane) were used separately. Physical and mechanical tests were conducted to determine the most effective material to coat the DPL fibers. To comprehensively assess the performance of the coated fibers, their morphology was examined via microstructure analysis using scanning electron microscopy (SEM) and energy dispersive X-ray analyses (EDX) tests. This analysis encompasses their material properties, chemical composition, water absorption, and degradation, providing a thorough understanding of the protective coatings’ impact on the DPL fibers. The tensile strength test results revealed that the maximum tensile strength of the bitumen coated date palm fi ber (DPLB) is 7.4 MPa. The tensile strength is two times greater than the polyurethane coated date palm leaf fiber (DPLP) and untreated date palm leaf fiber (UDPL). The results of the degradation test revealed that the weight loss percentage is equal to 45.5 and 25 in the case of the UDPL and DPLP fibers, and no loss in weight in the case of the DPLB fi ber. Out of all the test results, bitumen is considered the best due to its ability to resist the attack of chlorides and sulfate ionspresent in groundwater on top of being cheap, simple, and effi cient.